Sacrifice, Piss Christ, and Liberal Excess - D. Casey (Law Text Culture, 2000)
Andres Serrano's Piss Christ has been at the centre of one controversy or another for a decade. Much of the debate has focused on questions of tolerance and pluralism. The claim that Piss Christ is offensive to Christians seems to suggest, incorrectly I believe, that Piss Christ has neither place nor precedent within the Christian tradition. To the extent that Piss Christ questions the boundaries between the sacred and the profane, it enacts what it represents. It threatens the identity of conservative Christians who respond by seeking to exclude it from the public realm. I consider that what is at stake is not merely the question of tolerance within a pluralist society but also that of tolerance within a pluralist Church. To whom do religious symbols belong and who has the authority to prescribe the manner in which they are used? It will be my argument in this article that Piss Christ, regardless of authorial intention, is a profoundly religious work that speaks to the very heart of Christianity. Consequently, after ten years, Piss Christ is still worthy of consideration.